2021
DOI: 10.3390/app11167241
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Contamination in Different Food Service Units Associated with Food Handling

Abstract: Background: A microbiological analysis of samples taken from hands of food handlers and utensils/crockery in food service units was used to assess the risk of food contamination. We aimed to assess indicators of microbiological contamination in different food service units. Methods: We used data for an official inspection proposal (2018–2019) in different food service units serving a district in Northeast Portugal. We showed the proportion of positive samples for each microorganism assessed in samples taken fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Our study showed that the type of food establishment was associated with the rate of contamination, which is in accordance with the results of the study conducted by Alves et al [20] who found that the proportion of contamination varied according to the type of food service unit. The highest rate of contaminated samples was found in fishmongers, butcher shops/charcuteries, and pastry/bakery.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that the type of food establishment was associated with the rate of contamination, which is in accordance with the results of the study conducted by Alves et al [20] who found that the proportion of contamination varied according to the type of food service unit. The highest rate of contaminated samples was found in fishmongers, butcher shops/charcuteries, and pastry/bakery.…”
Section: Discussionsupporting
confidence: 93%
“…Nearly similar results were reported by (Bassyouni et al, 2012) who investigated S. aureus in 36.1% hand swabs of food handlers. While lower results were reported by (Castro et al, 2016;Beyene et al, 2019;Ahmed, 2020;Alves et al, 2021) in percentage of 11.1%, 11.3%, 25%, and 8.9%, respectively. These results revealed that food handlers play a great role in microbial contamination of food (Yap et al, 2019).…”
Section: Resultsmentioning
confidence: 58%
“…Indicator organisms are frequently used to detect whether contamination is absent or present or within unacceptable limits [ 21 , 22 ]. Total and fecal coliforms, Escherichia coli ( E. coli ), belonging to the Enterobacteriaceae family and Staphylococcus aureus are used as indicators to assess hygienic conditions [ 23 ]. SARS-CoV-2 viral RNA was found with a prevalence of 40.5% (95% CI: 27.4- 55.1%) in stool of COVID-19 patients [ 24 ].…”
Section: Introductionmentioning
confidence: 99%